Optimizing the establishment of an Intelligence Network in the Bauroso Group to actualize conducive public safety and order in the legal area of Batang Police Department - Nurmansyah, Muhammad Al Dhaffin Raevdha (Indonesian Journal of Police Studies, 2024)
The presence of the Bauroso Group inflicted public disturbance on Batang Regency which occurred due to the absence of an Intelligence network inside the group. This incident motivated the writer to do research with the focus on the establishment of an intelligence network by Batang Police Intelligence Company, with the use of qualitative approach with descriptive type research and with data gathering technique through observation, interview, and document study and analyze by POAC Theory, Management Theory, and 6M Theory and will be reviewed with Optimalization Concept, intelligence Network Concept, and Trust Concept. From the conducted research, there were found several findings that were not in accordance with the laws and regulations, which are human resources that are not suitable in terms of quantity and education, lack of budget, and a few differences with Perkabik No 5 year 2013 about establishment and mantainance of intelligence networks. And from those findings the writer analyzed factors that influence the establishment of intelligence network both internally and externally. So that is obtained things that influenced the intelligence network establishment. And by using optimalization and trust concepts, the problem solving is achived. Therefore, the writer suggests that in the future the Batang Police Intelligence Company will adhere to the guidelines for establishment of intelligence network and increase members knowledges and understanding of their duties so that conducive public safety and order in the Batang Police’s legal area can be achieved.